Em busca da organicidade: um estudo do fundo da Secretaria de Governo da Capitania de Minas Gerais - Marta Eloisa Melgaco Neves (1997)
The objective of this dissertation is the recognition and analysis of the concepts which oriented the process of elaboration of finding aids related to the holdings from the central colonial administration of the Captaincy of Minas Gerais, presently in the custody of the State Archives of Minas Gerais (Arquivo Público Mineiro). The sources used in developing the analysis of the active period of the records are two interconnected registers denominated Seção Colonial 03 (dating from 1754) and Seção Colonial 405 (dating from 1758). For the permanent archival period twelve finding aids published from 1896 through 1988 in the State Archives official journal (Revista do Arquivo Público Mineiro) are analyzed. The study permits the elaboration of an equivalency table which recuperates the original designations of the royal orders utilized in the Seção Colonial 03 book. An attempt is made at characterizing the uses to which the documents were put during both the active and permanent periods. Finally, the necessity of realizing further studies aimed at identifying the organic relationships underlying the documents and their potential as sources for both archival and historical research are emphasized.